Model Hidrologi Berbasis Data Satelit Untuk Analisis Banjir Studi Kasus Sub-Das Rokan Stasiun Pasir Pengaraian - Fitriani Fitriani; Sigit Sutikno; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Lubuh River which is located in the stems of Rokan Hulu Riau Province is one of the rivers that often have overflow water. Hydrology analysis is necessary to help the process of flood mitigation in Rokan Hulu. The advancement of technology in remote sensing has provide an alternative solution of data availability in hydrological modeling by using data obtained from the satellite. This research took the case study of AWLR station of Pasir Pengaraian in Rokan watershed with the length of the data in two conditions at the stage of no calibration. One condition for fourteen days (February 13, 2012 00:00 to February 26, 2012 period) and two conditions for six days (01 may 2012 00:00 to 06 may 2012 23:00 period). Based on the results at the beginning and the calibration process simulation, wave shape error after calibration is smaller than the initial simulation. While the value of the volume error and peak discharge error in the initial simulation is smaller than the calibrated value. The value of each parameter of the wave shape error, error and peak discharge volume error are 33.6176%, 8.6025%, and 5.8720% respectively at beginning of simulation in condition two and 0.0169%, 15.4120% and 28.7533% in the calibration process.  Keywords : hydrological modeling, flood analysis, satellite data, IFAS